Interpretation approaches towards delivering expressive musical performances (Case study Shah Alam) / Leonardo Sheik Isabel Sultan - Sultan, Leonardo Sheik Isabel (2013)
The purpose of this study is to discuss the approaches of interpretation used by students in their performance. To be more in depth, this study aims to investigate the relationship of imagination and expression in delivering performances as well to find out problems faced by students towards delivering expressive musical performances. This research is conducted by interviewing students and lecturers from Uitm Shah Alam . The methodology for this full study involves 9 questions that were specifically focused on imaginations and expressions as well other interpretation approaches. Besides that, this study also implies on jazz idiom, transcription of a recording by two different performances of the same piece will be analyzed and discussed regarding its rearrangement, articulation, harmony and other fundamentals that shows its applied in a jazz idiom. Which will be part of the findings in this study.